2013
DOI: 10.1016/j.jad.2012.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Topographic and sex-related differences in sleep spindles in major depressive disorder: A high-density EEG investigation

Abstract: Background Sleep spindles are believed to mediate several sleep-related functions including maintaining disconnection from the external environment during sleep, cortical development, and sleep-dependent memory consolidation. Prior studies that have examined sleep spindles in major depressive disorder (MDD) have not demonstrated consistent differences relative to control subjects, which may be due to sex-related variation and limited spatial resolution of spindle detection. Thus, this study sought to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 44 publications
4
67
1
Order By: Relevance
“…Spindles have been implicated in synaptic plasticity and sleepdependent memory consolidation in both humans and other animals (Sejnowski and Destexhe, 2000;Steriade, 2000;Gais et al, 2002;Schiffelholz and Aldenhoff, 2002;Miyamoto and Hensch, 2003;Steriade and Timofeev, 2003;Khazipov et al, 2004;Schabus et al, 2004;Hanlon et al, 2009;Diekelmann and Born, 2010;Fogel and Smith, 2011;Nir et al, 2011), partly because of the ability of thalamocortical spindles to trigger hippocampal sharp wave ripples (Siapas and Wilson, 1998;Sirota et al, 2003;Isomura et al, 2006;Mölle et al, 2006;Clemens et al, 2007Clemens et al, , 2010Nishida and Walker, 2007;Peyrache et al, 2009Peyrache et al, , 2011Johnson et al, 2010;Sullivan et al, 2011). Altered sleep spindle dynamics have been documented in several forms of mental disease (Ferrarelli et al, 2007(Ferrarelli et al, , 2010Vukadinovic, 2011;Wamsley et al, 2012;Wilson and Argyropoulos, 2012;Plante et al, 2013). However, it is not clear whether thalamocortical spindles regularly invade the hippocampus and affect its circuits outside sharp wave ripples, although several observations suggest that this might be the case (Sirota et al, 2003;Isomura et al, 2006;Nir et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Spindles have been implicated in synaptic plasticity and sleepdependent memory consolidation in both humans and other animals (Sejnowski and Destexhe, 2000;Steriade, 2000;Gais et al, 2002;Schiffelholz and Aldenhoff, 2002;Miyamoto and Hensch, 2003;Steriade and Timofeev, 2003;Khazipov et al, 2004;Schabus et al, 2004;Hanlon et al, 2009;Diekelmann and Born, 2010;Fogel and Smith, 2011;Nir et al, 2011), partly because of the ability of thalamocortical spindles to trigger hippocampal sharp wave ripples (Siapas and Wilson, 1998;Sirota et al, 2003;Isomura et al, 2006;Mölle et al, 2006;Clemens et al, 2007Clemens et al, , 2010Nishida and Walker, 2007;Peyrache et al, 2009Peyrache et al, , 2011Johnson et al, 2010;Sullivan et al, 2011). Altered sleep spindle dynamics have been documented in several forms of mental disease (Ferrarelli et al, 2007(Ferrarelli et al, , 2010Vukadinovic, 2011;Wamsley et al, 2012;Wilson and Argyropoulos, 2012;Plante et al, 2013). However, it is not clear whether thalamocortical spindles regularly invade the hippocampus and affect its circuits outside sharp wave ripples, although several observations suggest that this might be the case (Sirota et al, 2003;Isomura et al, 2006;Nir et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hereby a continuum model was proposed, suggesting that unusual non-clinical beliefs may represent a milder form of the positive symptoms found in severe mental illness (Lustenberger et al, 2015). Interestingly, first studies in adults with other mental diseases such as major depression reveal increased spindle density values (Plante et al, 2013), supporting a possible disease-specific character of sleep spindles. Future studies may further investigate the relationship between spindle measures and different dimensions of psychopathology to provide insight into the underlying neural circuits.…”
mentioning
confidence: 99%
“…Another sleep study on elderly depressed patients failed to find significant differences [25]. A recent high-density EEG, all-night study of 30 unmedicated MDD participants and 30 age-and gender-matched control subjects revealed significant increases in frontal and parietal sleep spindle density and ISA compared to controls [28]. Increases in frontal and parietal sleep spindle density, amplitude, duration, and ISA were driven by 19 MDD women, whereas the 11 men diagnosed with MDD showed either no differences or a decrease in spindle parameters.…”
Section: Sleep Spindle In Major Depressive Disordermentioning
confidence: 95%
“…The study of sleep spindle activity yielded very inconsistent results in subjects diagnosed with major depressive disorder (MDD), with no difference [11,24,25], a reduction [26,27], or even an increase [28] reported in MDD patients compared to control subjects. One of the studies that observed decreased sleep spindle activity in depression examined a cohort that was exclusively male and composed by a mixed sample including MDD and bipolar disorder (BD) [26].…”
Section: Sleep Spindle In Major Depressive Disordermentioning
confidence: 99%
See 1 more Smart Citation